Twice as dead [large type]: an Odelia Grey mystery - Jaffarian, Sue Ann, 1952- (Jaffarian, Sue Ann, 1952- Odelia Grey mystery., 2011)
Corpse magnet Odelia Grey is at it again, stumbling across a dead body at a wedding reception while "Achy Breaky Heart" plays in the background. Bodies are turning up so fast that Odelia enlists the help of her family and friends: Greg, Seth, Zee, Detective Frye, her half brother Clark, even her pompous boss Michael Steele. But solving a mystery is twice as hard when the victims have more secrets than the killer.